Law Enforcement through Justice and Ethical Institution: Historical Perspective - Aisyah, Siti; Ismail, Nurizal (AL-IKTISAB: Journal of Islamic Economic Law, 2018)
Islam is the way of life which guides mankind to attain the happiness in here and the hereafter (falah). It is also a religion of peace through the submission to the will and laws of God, advocates the establishment of ethic and social justice in order to achieve peace. In the history of Islam, enforcement of law was implemented to preserve good ethic and justice in the society. Therefore, it is needed to know how the implementation of Islamic law enforcement regarding ethic and justice in Islamic framework. This paper aims to study how the Islamic state in the early of Islam pays attention to ethic and justice of society in its government affair or administration and how the wilÄyat al mazÄlim and hisbah as Islamic institution will stand for law enforcement to promote justice and higher ethic in the society. Moreover, finding of the study states that the Justice and ethical values have been still concerned by Islamic State. The administration of justice carried out by Muslim should consist of the application of Shariâ€™ah in name of God without any temporal consideration. Enforcement of law regarding ethic and justice is manifested in hisbah and wilÄyat al-mazÄlim. Each institution has different duties, but has mutual relation to administrate the state toward welfare state. The hisbah institution plays its role to command good action (amar maâ€™ruf) and prohibit evil (nahi munkar). It has a responsible for the implementation of Shariâ€™ah principles in society. Furthermore, wilÄyat al-mazÄlim is an institution that carries out the justice around the society. This institution looks into the cases which are not included in common court authority, such as persecution matters which are committed by the authority, judges or member ruling family.